KEBEBASAN MANUSIA DALAM FILSAFAT EKSISTENSIALISME (STUDI KOMPARASI PEMIKIRAN MUHAMMAD IQBAL DAN JEAN PAUL SARTRE) - Elvira Purnamasari (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2017)
Talking about  freedom, freedom can have many meanings, depending on which  perspective it sees. If wrong  in looking,  then  the  freedom can  be  legitimacy  to do  something that  is not  good.  For this reason understanding freedom with proper  understanding becomes very important. Freedom in the philosophical view of existentialism is interesting to be examined since  this philosophy examines human beings  in terms  of their subjectivity so that it will provide an understanding of freedom not only philosophically which is theoretical but also in the ethical  realm  that really touches human life in real. The two figures whose thoughts are discussed in this study are representative of two different  schools  of existentialism, atheist  / non-religious existence and theistic  / religious existentialism. So this study will also present not only an understanding of freedom from an existentialist perspective but also  to see  how  a concept is viewed  by two  contradictory beliefs.  Muhammad Iqbal who built his thoughts with a firm belief in God and Jean Paul Sartre who tried to keep  people from being dependent on God with their atheistic  beliefs. The problem in this research, are: 1. How is human’s freedom in the philosophy of existentialism of Muhammad Iqbal and  Jean  Paul Sartre? 2. What are the similarities  and differences of the concept of human’s freedom according to Muhammad Iqbal and Jean Paul Sartre? To answer the  research  problem formulation above  is done  library research (library  research), by using  comparative method. The results of the research are: 1. Existentialism  Muhammad Iqbal is theistic existence of theistic. This characteristic of existentialism is very visible in the  idea  of “khudi” philosophy.  Khudi / self in Iqbal’s view is unique, free and creative. The freedom for him is a means to achieve the existence of the ultimate  self is man as niyabati divine/ representative of God on this earth. The existentialism of Jean Paul Sartre is representative of the atheistic  existentialism style. Because this concept departs from the idea that human’s freedom is absolute, then if there is a God man is not free. God’s power  will deprive human’s freedom. The foundation of Sartre’s concept of existentialism is that existence precedes the essence. Because man  is a self-conscious existence that he is free and responsible for his freedom. 2. The thoughts of these two figures have similarities,  namely  a) Equally look at human’s existence from the point of view subjectivity. So according to them  human’s existence is a free self and responsible for their actions. In other words, freedom is a human’s existence, b) His philosophy contains an ethical value that instills the importance of humanity. That every human being has responsibility is not only for himself but for all humans. The differences are: a) God’s existence in Iqbal’s view requires human’s existence, whereas for Sartre  the  existence of God eliminates the  existence of man  as an individual  who  has  absolute freedom, b) Iqbal’s freedom culminates in an approach to God as the vigerence of God. While Sartre’s freedom is an absolute freedom whose goal is purely freedom itself, the freedom to determine without being attached to anything, c) The freedom of others for Iqbal is a means of achieving true freedom. Meanwhile, Sartre argues that the freedom of others is a threat to his freedom.